Weed infestation and productivity of wheat crop sown in various cropping systems under conventional and conservation tillage - Minhas, Waqas Ahmed; Mumtaz, Naima; Ur-Rehman, Hafeez; Farooq, Shahid; Farooq, Muhammad; Ali, Hayssam M.; Hussain, Mubshar (Frontiers in Plant Science, 2023)
Climate change, pest infestation, and soil degradation are significantly reducing wheat (Triticum aestivum L.) yield. Wheat is cultivated in rice-wheat and cotton-wheat cropping systems and escalating global population is exerting substantial pressure on the efficiency of these systems. Conservation tillage and crop rotation could help in lowering soil degradation and pest infestation, and improving wheat yield. This three-year study evaluated soil properties, weed infestation and wheat yield under various tillage and cropping systems. Six different cropping systems, i.e., cotton-wheat, sorghum-wheat, mungbean-wheat, rice-wheat, sunflower-wheat, and fallow-wheat (control) and three tillage systems, i.e., conventional tillage (CT), zero-tillage (ZT) and minimum tillage (MT) were included in the study. The individual and interactive effects of tillage and cropping systems significantly affected soil properties, weed infestation and yield of wheat crop. Overall, CT resulted in lower soil bulk density and higher porosity, while ZT behaved oppositely at all locations in this regard. Similarly, mungbean-wheat cropping system resulted in lower bulk density and higher porosity and nitrogen (N) contents, while fallow-wheat cropping system resulted in higher bulk density, and lower soil porosity and N contents. Similarly, ZT and CT resulted in higher and lower weed infestation, respectively. Likewise, lower and higher weed density and biomass were recorded in wheat-sorghum and wheat-fallow cropping systems, respectively at all locations. In the same way higher number of productive tillers, number of grains per spike, 1000-grain weight, grain yield, and economic returns of wheat crop were recorded for CT, whereas ZT resulted in lower values of these traits. Regarding interactions, wheat-mungbean cropping system with CT resulted in lower bulk density and higher porosity and N contents, whereas wheat-fallow system with ZT behaved oppositely at all locations in this regard. Similarly, higher and lower values for yield-related traits and economic returns of wheat crop were noted for mungbeanwheat cropping system under CT and fallow-wheat and sorghum-wheat cropping systems under ZT, respectively. It is concluded that the mungbean-wheat cropping system improved wheat productivity and soil health and sorghum-wheat cropping system could lower weed infestation. Therefore, these cropping systems can be practiced to lower weed infestation and improve wheat yield and economic returns.